Long-term follow-up after purine analogue therapy in hairy cell leukaemia. Issue 4 (December 2015) - Else, Monica; Dearden, Claire E.; Catovsky, Daniel
Abstract: Since 2006 when we last reviewed the literature concerning the use of purine analogues in hairy cell leukaemia (HCL), results from several new and updated series have been published. Here we examine these reports and consider their implications for patient management. The two purine analogues pentostatin and cladribine remain the first-line treatments of choice for all patients with HCL. Although they have not been compared in randomised trials, they appear to be equally effective. A complete response is important for the long-term outcome and we look at how best this can be achieved. Evidence is emerging which supports the use of either purine analogue plus an anti-CD20 monoclonal antibody after relapse, though questions remain concerning the scheduling of the monoclonal antibody. Patients refractory to the purine analogues may require alternative agents.